Generation of seal influenza virus variants pathogenic for chickens, because of hemagglutinin cleavage site changes. - Li, S Q (1990)
Influenza virus A/seal/Mass/1/80 (H7N7) was adapted to grow in MDCK cells and chicken embryo cells (CEC) in the absence of exogenous protease. The biological properties of the virus variants obtained coincided with intracellular activation of the hemagglutinin (HA) by posttranslational proteolytic cleavage and depended on the cell type used for adaptation. MDCK cell-adapted variants contained point mutations in regions of the HA more distant from the cleavage site. It is proposed that these mutations are probably responsible, through an unknown mechanism, for enhanced cleavability of HA in MDCK cells. Such virus variants were apathogenic in chickens. CEC-adapted variants, on the other hand, contained an insertion of basic amino acids at the HA cleavage site, in addition to scattered point mutations. The insertions converted the cleavage sites in the variant virus HAs so that they came to resemble the cleavage site found in highly pathogenic avian influenza viruses. CEC variants with such cleavage site modifications were highly pathogenic for chickens. The lethal outcome of the infection in chickens demonstrated for the first time that an influenza virus derived from a mammalian species can be modified during adaptation to a new cell type to such an extent that the resulting virus variant becomes pathogenic for an avian species.